Bovine endometrial stromal cells display osteogenic properties - Cavirani Sandro; Capocefalo Antonio; Franceschi Valentina; Donofrio Gaetano; Sheldon Iain (BMC, 2008)
Abstract The endometrium is central to mammalian fertility. The endometrial stromal cells are very dynamic, growing and differentiating throughout the estrous cycle and pregnancy. In humans, stromal cells appear to have progenitor or stem cell capabilities and the cells can even differentiate into bone. It is not clear whether bovine endometrial stromal cells exhibit a similar phenotypic plasticity. So, the present study tested the hypothesis that bovine endometrial stromal cells could be differentiated along an osteogenic lineage. Pure populations of bovine stromal cells were isolated from the endometrium. The endometrial stromal cell phenotype was confirmed by morphology, prostaglandin secretion, and susceptibility to viral infection. However, cultivation of the cells in standard endometrial cell culture medium lead to a mesenchymal phenotype similar to that of bovine bone marrow cells. Furthermore, the endometrial stromal cells developed signs of osteogenesis, such as alizarin positive nodules. When the stromal cells were cultured in a specific osteogenic medium the cells rapidly developed the characteristics of mineralized bone. In conclusion, the present study has identified that stromal cells from the bovine endometrium show a capability for phenotype plasticity similar to mesenchymal progenitor cells. These observations pave the way for further investigation of the mechanisms of stroma cell differentiation in the bovine reproductive tract.